Simulation of the Lightweight Ceramic/Aluminum Alloy Composite Armor for Optimizing Component Thickness Ratios - Chang, Z.-L.; Zhao, W.-L.; Zou, G.-P.; Sun, H.-Q. (Проблемы прочности, 2019)
The lightweight ceramic/aluminum alloy composite armor design is examined and optimized to get better protective performance. The armor penetrability is simulated via the smooth particle hydromechanics approach using the ANSYS/AUTODYN software. The accuracy of the program was verified by comparing with known data. Three composite armor types with the total thickness of 30, 40, and 50 mm, and five different ceramic/metal thickness ratios were analyzed in simulation of the residual bullet speed and the final distance. Simulation results are compared with the theoretical model. The best bullet protective performance of the three armor types was obtained with the ceramic/aluminum alloy thickness ratio of 4:1.